Micro-Blogging System Based on Geographic Information in Google Map - Zhiqiang You; Huaiyu Xu; Jihui Xu; Jinfeng Xu; Dayu Shi (2012 4th International Conference on Computational Intelligence and Communication Networks, 2012)
This paper discussed the development of domestic Micro-blogging and analyzed the status in the future. Moreover, it involves a number of technical difficulties encounters, including how to make further development based on the open source framework Status Net, and how to create HTML language based on object-oriented programming using PHP and how to use Google Map API. Then, we combine the requirements of Micro-blogging and Google map service to build the system architecture and implement this system. In this system you can view information, distribute information, reply information, forward information and search information according to Google Map service. And the most important is that our system provides a platform that enables users to communicate with the Google map, and allows users to locate any place to send messages to increase the users' experience and flexibility.